Effect of Solder Layer Void Damage on the Temperature of IGBT Modules - Pengpeng Xu; Peisheng Liu; Lei Yan; Zhao Zhang (Micromachines, 2023)
Solder layer void is one of the main failure causes of power semiconductor devices, which will seriously affect the reliability of the devices. In this study, a 3D model of IGBT (Insulated Gate Bipolar Transistor) packaging was built by DesignModeler. Based on ANSYS Workbench, the influence of void size, location, solder layer type, and thickness on the temperature distribution of the IGBT module was simulated. The results show that the larger the void radius, the higher the temperature of the IGBT module. The closer the void is to the center of the solder layer, the higher the temperature of the module. The void on the top corner of the solder layer had the greatest impact on the junction temperature of the IGBT module, and the shape of the void is also one of the factors that affect the temperature of the module. The denser the void distribution, the higher the temperature of the module. The temperature of the IGBT module was reduced from 62.656 °C to 59.697 °C by using nanosilver solder paste, and the overall heat dissipation performance of the module was improved by 5%. The temperature of the module increased linearly with the increase in solder layer thickness, and the temperature increased by 0.8 °C for every 0.025 mm increase in solder layer thickness. The simulation results have a guiding significance for improving the thermal stability of IGBT modules.